Electrochemical Properties of Diluted Al-Mg Alloys With Columnar-To-Equiaxed Transition - Román, Alejandra Silvina; Ibañez, Edgar Rolando; Méndez, Claudia Marcela; Pedrozo, Marianela; Kramer, Gustavo Raúl; Zadorozne, Natalia Silvina; Alonso, Paula Regina; Ares, Alicia Esther (Frontiers in Materials, 2022)
The objective of the present research is to study the corrosion susceptibility of two Al-Mg diluted alloys (Al-0.5wt.%Mg and Al-2wt.%Mg) with different grains structures obtained by directional solidification (columnar, equiaxed and columnar-to-equiaxed transition, CET) in 0.5% NaCl solution, at room temperature. The corrosion resistance is analyzed by potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques in both longitudinal and transversal sections of the samples. The columnar grain zone presents higher corrosion resistance than the equiaxed grain zone. In addition, the transversal section shows higher corrosion resistance than the longitudinal section of the samples. Then, the Al-0.5wt.% Mg alloy displays higher corrosion resistance than the Al-2wt.% Mg alloy. The values of the polarization resistance are used as a basic criterion for the evaluation of the corrosion resistance of both alloys. In this way, when the polarization resistance decreases with the increasing in the distance from the base, the grain size, secondary dendritic arm spacings and hardness increases. In addition, when the polarization resistance increases, the critical temperature gradient decreases.